Angka Kuman Udara di Ruang Rawat Inap Rumah Sakit - Claudia Aillen Lomboan; Jootje M.L. Umboh; Woodford Baren Joseph (Universitas Sam Ratulangi, 2020)
Background: In-patient ward is vulnerable to infectious diseases due to hospital activities. An infectious disease often encountered in hospitals is a nosocomial infection caused by germs. The most potentially potential source causes nosocomial infections in the treatment rooms, medical tools and air. The purpose of this research was to measure the microbial density rate in each in-patient ward on the Hospital Level IV LANUD Sam Ratulangi Manado. Method: A cross-sectional study has been conducted in in-patient wards of Hospital Level IV LANUD Sam Ratulangi Manado. The microbial density rate of indoor air in seven in-patient wards (male room class 2, male room class 3, female room class 2, female room class 3, children room class 2, children room class 3, and general inpatient room) were measured two times (morning, and before sunset) at three different sampling sites of each room. Result: The results show that the microbial density rate between 505,5-1916 CFU/m2.The highest rate was found in female room class 2 and the lowest rate was found in general inpatient room. Conclusion: In conclusion, the microbial density rate between 505,5-1916 CFU/m2 and there was 100% quality of air do not comply with the health requirements as regulated in the Ministry of Health Decision of 1204/MENKES/ SK/X/2004.